THE ROLE OF INTERNATIONAL TRADE AGREEMENTS ON THE COMPETITIVENESS OF THE VIETNAMESE CLOTHING INDUSTRY - Atina Izza (Universitas Nasional, 2023)
The clothing industry is a labor-intensive industry and many developing countries like it as a quick way towards industrialization. The clothing industry can absorb large amounts of labor and reduce unemployment as it creates jobs for unskilled labor. Therefore, the clothing industry is seen as ounces of way of reducing a country's poverty and bringing economic growth. The end of the Multi-Fibre Arrangement in 2005 transformed the global framework, marked by the expansion of global value chains and production networks, making competition in the international apparel market more intense. As a result, maintaining international competitiveness is crucial for success in the international clothing industry. Vietnam, as a developing nation, has experienced substantial economic growth and has become a strong competitor for other developing countries in attracting foreign direct investment. This study aims to investigate the impact of international trade agreements on Vietnam’s competitiveness in the international economy, providing insights into how the country has been able to maintain its competitiveness in the challenging global apparel market.